The Outcome of an elephant translocation from Isiolo to Tsavo East National Park, Kenya - Lydia Tiller; Lucy King; Fredrick Lala; Frank Pope; Chris Thouless; Jake Wall; Iain Douglas-Hamilton (Pachyderm)
This management piece documents the outcome of an elephant translocation from Isiolo to Tsavo East National Park, Kenya in November 2021. The translocation aimed to reduce human-elephant conflict in the area and to prevent any retaliation toward the elephants. This was achieved by removing the ‘problem elephant group’, however the aim of resettling the elephants in Tsavo was not achieved, as the group fragmented and some swiftly moved far outside release site. Two elephants, which we were able to monitor through satellite collars, exhibited homing behaviour and both left Tsavo East National Park within 1-7 weeks of being released. If translocation continues to be the method of choice for problem elephants, there is a need for thorough planning and sound science to inform future operations, which should include collaring of each individual. Trained personnel and substantial budgeting for post release monitoring, and any potential conflict-reduction interventions, are therefore key management considerations for ensuring the health and wellbeing of translocated elephants in the future. In the long-term, focusing mitigation management on a larger number of habitual crop-raiders will have more impact and be a more effective approach for elephant managers. This could involve better spatial land-use planning, maintenance of corridors between protected areas, negative conditioning tactics and maintenance and upgrading of barriers.